Lymphangiogenesis and tumor metastasis - Rovenská, Eva; Kovářová, Mária (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2015)
The review article is focused on lymphangiogenesis and on metastatic spread of tumor cells via the lymphatic vessels. Numerous new lymphatic vessels (especially lymphatic capillaries) are formed in the tumors and in their nearby location during lymphangiogenesis. Tumor cells can enter the lymphatic capillaries through existing specially opening connections in the capillaries walls between their endothelial cells. These are not connected with connecting complexes. When opened, the opening is a few micrometers wide. These specialized connections are named the same as the primary valves. Tumor cells can also erode lymphatic vessels and create larger incoherence directly in their vessel wall of endothelial cells. Lymphangiogenesis is induced by vascular endothelial growth factors VEGF-C/-D and VEGF-3. On the basis of lymphangiogenesis research in experimental animals, clinical and laboratory observations in humans, some scientists suggest that anti-lymphangiogenesis treatment could be beneficial for patients who are at risk of metastases from tumors passing through lymphatic vessels.
Keywords: lymphangiogenesis; metastases; tumors; anti-lymphangiogenesis treatment